Pengaruh Promosi Melalui Media Sosial dan Saluran Distribusi Terhadap Minat Beli Konsumen di Era Pandemi Studi Pada Ramio Cafe And Mart di Sumenep - Firda Ramadayanti; Nirma Kurriwati (Management Department of Economics and Business Of Trunojoyo Madura University, 2021)
The spread of various industries in Indonesia today makes people become more consumptive. The current digital era demands that companies increasingly compete to attract customers and expand their business development areas, for example by utilizing advanced technology and the internet. Ramio Cafe and Mart is one of the restaurants in Sumenep. Precisely located on Jl. Dr. Cipto Kolor, Sumenep City, Sumenep Regency, East Java 69417. Covid-19 which has an impact on various sectors, especially the culinary sector, has made Ramio Cafe and Mart experience a decline in turnover since the pandemic and the implementation of PSBB. This type of research is a survey research with a quantitative approach. The population of this study are consumers of Ramio Cafe and Mart. The sampling technique used accidental sampling and obtained a sample of 30 people. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique used is the classical assumption test, multiple linear regression and hypothesis testing. The results showed that promotion and distribution channels partially and simultaneously had a significant positive effect on consumer buying interest.